Securitization of Islam: A Case of Muslims in Cyprus - Riskiansyah Ramadhan (AJIS: Academic Journal of Islamic Studies, 2020)
This paper analyzes how Muslims, as a religious community in the Republic of Cyprus, became an object of discrimination. Furthermore, the paper tries to understand and describe how Muslims’ daily lives are as a minority in the country through a case study approach. The study found that Islamophobic incidents often occur in the form of hate speech and discrimination in the workplace, schools, and even government institutions. These Islamophobic behaviors are an attempt to securitize Islam on the island. Moreover, prominent figures like political and religious leaders actively contribute to the phenomena of this securitization. Although religious freedom is protected by law, the Christian Greek Cypriot is not ready to accept multiculturalism. Thus, both government and society, and the community must support each other in bringing about peace in the country